2016
DOI: 10.1002/1873-3468.12496
|View full text |Cite
|
Sign up to set email alerts
|

Both bulk and cancer stem cell subpopulations in triple‐negative breast cancer are susceptible to Wnt, HDAC, and ERα coinhibition

Abstract: Development of targeted therapies for triple-negative breast cancer (TNBC, a more aggressive subtype) is an unmet medical need. We analyzed data from 887 patients with invasive breast cancer and observed that increased Wnt and histone deacetylase (HDAC) activities are associated with estrogen receptor 1 (ESR1) and progesterone receptor (PGR) repression, poor survival, and increased relapse. The inverse correlation between Wnt signaling and repression of ESR1 and PGR expression was found to be magnified in canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 44 publications
0
38
0
Order By: Relevance
“…Normal mammary tissues or areas containing tumor were identified by gross pathologic examinations. Approximately 2 mm cores were obtained using a sterile biopsy punch that was further sliced with a scalpel to obtain approximately 2 × 1 mm tumor slices (Dayekh et al ., ; Sulaiman et al ., ). The slices were randomized, and three slices were placed into each well of 24‐well plate and cultured in DMEM‐F12 medium supplemented with 10% FBS, 1% penicillin/streptomycin, 1 μg·mL −1 insulin, 0.5 ng·mL −1 hydrocortisol, and 3 ng·mL −1 epidermal growth factor.…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…Normal mammary tissues or areas containing tumor were identified by gross pathologic examinations. Approximately 2 mm cores were obtained using a sterile biopsy punch that was further sliced with a scalpel to obtain approximately 2 × 1 mm tumor slices (Dayekh et al ., ; Sulaiman et al ., ). The slices were randomized, and three slices were placed into each well of 24‐well plate and cultured in DMEM‐F12 medium supplemented with 10% FBS, 1% penicillin/streptomycin, 1 μg·mL −1 insulin, 0.5 ng·mL −1 hydrocortisol, and 3 ng·mL −1 epidermal growth factor.…”
Section: Methodsmentioning
confidence: 97%
“…Total RNA was extracted using RNeasy kit (Qiagen, Toronto, ON, Canada) and real‐time qPCR (RT‐qPCR) analysis was performed using Bio‐Rad MyiQ (Bio‐Rad) as previously described (Jia et al ., ; Sulaiman et al ., ). The conditions for RT‐qPCR reactions were one cycle at 95 °C for 20 s followed by 45 cycles at 95 °C for 3‐s and annealing at 60 °C for 30 s. Results were normalized to the housekeeping gene 18S ribosomal RNA (18S) or GAPDH.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Hsieh et al showed that HDAC3 was linked to CSC homeostasis by increasing β‐catenin expression through the Akt/glycogen synthase kinase 3β pathway. Other preclinical models also have shown the impact of HDACi on CSCs …”
Section: Epigeneticsmentioning
confidence: 99%
“…Also, due to the non‐expression of receptors TNBCs have an inferior prognosis. However, Sulaiman et al [] when analyzed the data from 887 invasive TNBC breast cancer patients observed an increased Wnt, HDAC that was associated with upregulation of oestrogen receptor 1 (ESR1) and repression of progesterone receptor (PGFR), more relapse and hence, reduced survival. Accordingly, one strategy by co‐suppressing Wnt, HDAC, and ESR1 in TNBC cell lines using clinically relevant low dose inhibitors could effectively repress both CSC subpopulations and cancer cells and also reverted CSCs to non‐CSC populations.…”
Section: Approaches Toward Cancer Stem Cell Therapeuticsmentioning
confidence: 99%